Dihydromyricetin Attenuates Streptozotocin‐induced Liver Injury and Inflammation in Rats via Regulation of NF‐κB and AMPK Signaling Pathway. Issue 2 (19th February 2020) - Chen, Lei; Yao, Maojun; Fan, Xiaoyun; Lin, Xiujun; Arroo, Randolph; Silva, Aline; Sungthong, Bunleu; Dragan, Simona; Paoli, Paolo; Wang, Shaoyun; Teng, Hui; Xiao, Jianbo
Abstract : Dihydromyricetin (DHM) dramatically improved the quality of life for Streptozotocin (STZ)‐induced diabetic rats and significantly increased the activity of antioxidant enzymes in the liver. Moreover, DHM successfully ameliorated diabetes‐induced liver damage by suppression of apoptosis in the liver, as indicated by the decreased levels of Bax and cleaved caspase‐3. In diabetic rats, the levels of tumor necrosis factor‐ α and interleukin‐1 β in the liver were significantly increased. However, the administration of DHM (100–400 mg/kg/day) for 6 weeks restored the cytokine levels to their normal values in a dose‐dependent manner in diabetic rats by the regulation of nuclear factor‐kappa B signaling pathway. In addition, DHM significantly induced 5′ AMP‐activated protein kinase (AMPK) phosphorylation and decreased MyD88, TLR4, p38, GSK‐3 β protein expression levels in the liver of diabetic rats. In conclusion, DHM could improve STZ‐induced liver impairment by preventing oxidative stress, apoptosis, and inflammation.